LncRNA FAM83A‐AS1 promotes lung adenocarcinoma progression by enhancing the pre‐mRNA stability of FAM83A - Wang, Wenyi (John Wiley & Sons Australia, Ltd, 2021)

(untitled) (Thorac Cancer)
BACKGROUND: Lung cancer is the leading cause of cancer deaths worldwide. Long non‐coding RNAs (lncRNAs) affect a series of cellular biological processes, including oncogene function promotion. In this study, we explored the functions and mechanisms of FAM83A antisense RNA 1 (FAM83A‐AS1) in non‐small cell lung cancer (NSCLC) progression. METHODS: The expression of FAM83A‐AS1and FAM83A mRNA was analyzed using the Cancer Genome Atlas (TCGA) data. Proliferation, migration, invasion and Western blotting were measured after treatment with overexpressed or knockdown FAM83A‐AS1. To determine the relationship between FAM83A‐AS1 and FAM83A, RNase protection assay (RPA), amanitin treatment, RNA pulldown assay and RNA immunoprecipitation (RIP) assay were performed. RESULTS: High expression of FAM83A‐AS1 in lung adenocarcinoma (LUAD) was closely associated with low overall survival (OS) and progression‐free survival (PFS). Functionally, high FAM83A‐AS1 expression increased LUAD cell proliferation and metastasis, indicating that FAM83A‐AS1 exerted its oncogenic functions. Furthermore, FAM83A‐AS1 promoted NSCLC progression via ERK signaling pathways. Mechanistically, FAM83A‐AS1 post‐transcriptionally increased FAM83A expression by enhancing pre‐mRNA stability. FAM83A‐AS1 enhanced FAM83A mRNA stability not only by forming an RNA duplex but also by binding to FBL. CONCLUSIONS: We determined that FAM83A‐AS1 increased FAM83A expression by enhancing FAM83A pre‐mRNA stability and promoted the tumorigenesis of LUAD.